ESTIMASI CADANGAN KLAIM MENGGUNAKAN METODE DETERMINISTIK DAN STOKASTIK - Yuciana Wilandari; Gunardi Gunardi; Adhitya Ronnie Effendie (Jurnal Statistika Universitas Muhammadiyah Semarang, 2021)
The estimated of claims reserve has a very important in insurance companies, because it is the company's liability to policyholders in the future and can also result in the bankruptcy of the insurance company. In general, there are two methods for calculating claims reserves are the deterministic method (Chain Ladder and Bornhuetter Ferguson) and the stochastic method (Benktander Hovinen and Cape Cod). This article compares the two methods and determines the best method. Using the claim payments data that have been paid by an insurance company in Indonesia, the best method is the Benktander Hovinen method.